Impacts of climate change on the maritime industry part 3 of 3 - increasing natural disasters - Teo, Jason Hee Lye. (2011)
Climate change had been the main topic in the recent years. Greenhouse gases emission is one of the causes for climate change. The impacts of the climate change are usually undesirable. Increase in natural disasters, one of the effects of climate change is identified and will be discussed in this report. The implied impacts of the increase in natural disasters were identified from our literature review and strategies for the impacts were suggested. A set of suggested strategies was formed with the viewpoints from other maritime industrial players collected from questionnaires and interviews. 200 maritime industrial players from the shipping sector and the port sector were contacted for a survey and 23 of them responded to our survey. The survey aims to find out if the maritime industrial players were affected by the implied impacts and the severity of the implied impacts. Those surveyed were also asked to rate the effectiveness of our suggested strategies.